2001
DOI: 10.1111/j.1469-7793.2001.0811e.x
|View full text |Cite
|
Sign up to set email alerts
|

Spino‐bulbo‐spinal pathway mediating vagal modulation of nociceptive‐neuroendocrine control of inflammation in the rat

Abstract: Stimulation of nociceptors by intradermal capsaicin produces depression of bradykinin (BK)-induced synovial plasma extravasation (PE) that is markedly enhanced by subdiaphragmatic vagotomy. This depression is mediated by the adrenal medullae, a propriospinal pathway between the afferent nociceptive input and preganglionic neurones projecting to the adrenal medullae, and a spino-bulbo-spinal pathway. Here we investigated the role of spinal ascending and descending pathways in the interaction between noxious and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(1 citation statement)
references
References 39 publications
(73 reference statements)
1
0
0
Order By: Relevance
“…This unexpected reduction of microglial activity may be explained by vagal inhibition of spinal sensory signaling. It has been previously demonstrated that vagal activity influences a pathway of descending inhibition from the hindbrain—presumably the NTS—to the spinal afferent terminals in the dorsal horns of the SC [30;31]. The subdiaphragmatic vagotomy performed in our study would disrupt the same descending pathway.…”
Section: Discussionsupporting
confidence: 52%
“…This unexpected reduction of microglial activity may be explained by vagal inhibition of spinal sensory signaling. It has been previously demonstrated that vagal activity influences a pathway of descending inhibition from the hindbrain—presumably the NTS—to the spinal afferent terminals in the dorsal horns of the SC [30;31]. The subdiaphragmatic vagotomy performed in our study would disrupt the same descending pathway.…”
Section: Discussionsupporting
confidence: 52%